2022
DOI: 10.1002/jgc4.1632
|View full text |Cite
|
Sign up to set email alerts
|

Latinx attitudes, barriers, and experiences with genetic counseling and testing: A systematic review

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 150 publications
0
2
0
Order By: Relevance
“…A key finding was that GUÍA was most helpful in increasing understanding outcomes for the H/L population in our study. These results suggest that GUÍA may be a useful and beneficial tool for counseling individuals of H/L descent, who currently represent almost 19% of the US population(33) yet for whom research has demonstrated significant unmet needs in genomic medicine (34). Interestingly, GUÍA's effectiveness in the H/L population was attenuated when a medical interpreter was used for result disclosure.…”
Section: Discussionmentioning
confidence: 96%
“…A key finding was that GUÍA was most helpful in increasing understanding outcomes for the H/L population in our study. These results suggest that GUÍA may be a useful and beneficial tool for counseling individuals of H/L descent, who currently represent almost 19% of the US population(33) yet for whom research has demonstrated significant unmet needs in genomic medicine (34). Interestingly, GUÍA's effectiveness in the H/L population was attenuated when a medical interpreter was used for result disclosure.…”
Section: Discussionmentioning
confidence: 96%
“…Prior studies report low awareness and uptake of genetic testing services for inherited cancers among the Hispanic/Latino (H/L) populations in the United States [ 2 ], who comprise more than 18% of the population and represent the largest minority group. Despite the low awareness, studies suggest once aware, H/L individuals are interested in learning more about inherited cancer and testing [ 3 ]. However, access to these services by Spanish speakers is limited due to a multitude of barriers including a dearth of Spanish-speaking genetic counselors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%